Migráció és indetitás : vajdasági egyetemisták Magyarországon - Rózsa, Rita (Közép-Európai Közlemények, 2011)
For many years Vojvodina has been a home of different nationalities. This area has always been populated by multiracial people, which were sometimes affected by immigrants and settlers. According to the census between the two World Wars the population increased by a few myriad people that were mainly migrants, but the natural growth also influenced the process. Nowadays the situation is not so bright, because the population of Vojvodina, especially the number of Hungarians, is constantly decreasing. During my research I wanted to ascertain whether the loss of positions on the labour market among the Hungarians is noticeable. I was interested in the supportive familial back-ground, the emotional and intellectual approach in connection with the host country, and whether the country’s reception helped reaching their goals. How and where do the intellectuals imagine their future, which are the reasons of migration and the setbacks of returning? Has their identity altered in any ways? Would they come back to Vojvodina if the economic and political situation changed?